The Human Being Perspective in the Buddhist Philosophy - Katatecho, Phramahasomchai; ปัญจยวัฒนคุณ จิตศริณย์พร; Chaiya, Wanitchaya (Journal of Dhamma for Life, 2022)
This academic article aims to present the concept of human beings in Buddhist philosophy. Philosophy is a concept about man and nature, a concept that is extremely important to know the truth of life. Buddhist philosophy is represented by a doctrine of truth (truth) and practice (ethics). Buddhist philosophy says Human beings do not only have the body, which is the aggregate, but also the mind. Which is the name Khan and regards the body and the mind as being each of their own nature or characteristics. It is the mind that has its own nature that cannot be transformed into matter, and that matter that can be transformed into energy cannot be transformed into mind. The human being, according to philosophy, therefore consists of two elements: concrete and abstract currents. Buddhist philosophy has a view that the human body is impermanent (impermanent) and suffering (dukkha) because it is constantly changing as for the human mind, there are also changes in birth and extinction.